POSSIBILITIES OF USING INNOVATIVE STRATEGIES IN TOURISM DEVELOPMENT - Jo'raeva Feruza Jumaqulovna (Journal Park Publishing, 2023)
Tourism has become an essential pillar of economic growth and cultural exchange in today’s globalized world. As destinations strive to attract more visitors and create memorable experiences, the importance of embracing innovative strategies in tourism development cannot be overstated. This article explores the possibilities and potential benefits that arise from the integration of innovative approaches in the tourism industry.
Keywords: innovative strategies, tourism development, possibilities, technology, sustainability, digitalization, experiential tourism, community engagement, destination marketing, data analytics, augmented reality, virtual reality.